Lipid Abnormalities in the Natural History of Diabetes (Journal of Medicine, 2015)
Objective: To explore lipid abnormalities in normoglycemic first-degree diabetic relatives (FDRs) and prediabetic and diabetic subjects in the natural history of diabetes.Research design and methods: Thirty six impaired fasting glucose (IFG), 61 isolated impaired glucose tolerance (I-IGT), 64 combined IFG-IGT, 73 diabetic, and 32 FDRs along with 57 normoglycemic healthy controls without family history of diabetes in 1st degree relatives, were selected purposively following 2003 ADA cut-off values and 2006 WHO/IDF grouping. Anthropometry and blood pressure of the subjects were taken. Fasting and 2-h plasma glucose and HbA1C were measured. Fasting plasma triglyceride, total cholesterol and HDL cholesterol were measured by enzymatic colorimetric method.Results: Serum triglyceride was higher in IFG, I-IGT, IFG-IGT, diabetic and FDRs compared to Control [145 (59- 307), 128 (66-584), 166 (68-764), 161 (69-750) and 130 (81-281) vs. 108 (47-219) mg/dl, P